Effects of country-level legal, extra-legal and political institutions on auditing: A cross-country analysis of the auditor specialization premium - Srinidhi, B.; Lim, C.; Hossain, Mahmud (Elsevier, 2009)
In this cross-country study of the specialist auditor premium, which spans the US and 12 other countries, we provide evidence that country-level institutional strength increases average audit fees, but reduces the incremental demand for specialist auditors. This finding supports the hypothesis that strong institutions and the demand for specialist knowledge act as substitutes in providing the requisite assurance of financial statements.